Proses Media Relations pada Holding Pangan BUMN ID FOOD - Elisabeth Mirza Giesella Putri; Fathiya Nur Rahmi (Universitas Gadjah Mada, 2023)
This study describes the process of media relations at the Holding Company of FOOD SOE ID FOOD. Judging from the media monitoring scoring award assessed by the Ministry of SOEs, ID FOOD was ranked first for the fertilizer and food cluster in November 2022. ID FOOD also set a target for media monitoring scoring, namely to be ranked first or second in the fertilizer and food cluster. As a Holding company of food SOE, ID FOOD has a lot of publicity which is evident from ID FOOD's scoring position, which is in first and second place. This study aims to determine the media relations process carried out by the Holding Company of FOOD SOE ID FOOD to obtain publicity in the period January 2022 - January 2023. The research method used is descriptive qualitative, using interview data collection techniques. This research shows the results that ID FOOD carries out media relations activities such as the distribution of press releases, personal approaches to the media, as well as media visits which are carried out in order to maintain good relations between the media and the company. Process media relations, from planning to evaluation, has been carried out by ID FOOD, to get publicity about the company's performance in external media.